Pengaruh Kemampuan Literasi Digital Terhadap Hasil Belajar Matematika Murid - Vera Cahyani; Siska. S; Wafiq Fatimah Azzahrah; Asdar Dollo (Pusat Studi Bahasa dan Publikasi Ilmiah, 2026)
This study aims to examine the effect of digital literacy on the mathematics learning outcomes of eighth-grade students at SMP Negeri 1 Parepare. Digital literacy in this context encompasses students’ ability to access, evaluate, and utilize digital information in mathematics learning. The study employed a quantitative approach with an ex post facto correlational design. Data were collected through a digital literacy questionnaire and documentation of students’ midterm examination scores, and subsequently analyzed using simple linear regression. The results indicate that digital literacy has a positive and statistically significant effect on mathematics learning outcomes (t = 2.102; p = 0.040). However, the magnitude of its contribution is relatively low, as reflected by the coefficient of determination (R² = 0.069), suggesting that only 6.9% of the variance in learning outcomes is explained by digital literacy. The regression model was also found to be statistically significant simultaneously (F = 4.418; p = 0.040). In conclusion, while digital literacy significantly influences mathematics learning outcomes, its effect remains limited. Therefore, it should be integrated with other pedagogical factors to more effectively enhance students’ academic achievement.